The great task remaining before us : Reconstruction as America's continuing Civil War - Cimbala, Paul A. (Paul Alan), 1951-; Miller, Randall M. (Reconstructing America (Series), 2010)
Using case studies, this book remaps considerations of the Civil War and Reconstruction era by charting the ways in which the needs, interests, and experiences of going to war, fighting it, and making sense of it informed and directed politics, public life, social change, and cultural memory after the war's end.